Pelatihan Penyusunan Laporan Keuangan Di Kelurahan Cibubur Jakarta Timur - Samsul Arifin; Egita Sari Br Tarigan (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
Village is the smallest unit of local government, as an integral part of government accounting district or city in NKRI, then village financial accountability should be regulated nationally. Accountability is one of the principles in village administration. Accountability must be generally accepted, so the means of accountability need to be regulated by natioanl standars. Financial management is one of the important aspects for the progress of the institution. As long as the institution still uses money as a transaction tool, accounting is needed by the institution.Accounting will provide several benefits, among others: know the position of funds both source and use, make the right budget, calculate taxes and know the cash flow over a certain period. The use of accounting can support the achievement of good corporate governance (GCG) especially in terms of financial management. Based on the above it is necessary to conduct training for employess in the kelurahan in terms of managing finances and prepare financial reports using accounting. The training program offered is in the form of simple accounting training for kelurahan employees and can be immediately applied in operational activities.